Migration, adolescents and health. (30th September 2020) - Devakumar, D
Abstract: In low- and middle-income countries, migration for work is common but the health consequences on adolescents is poorly understood. Particularly in low-resource settings, when children enter their adolescent years, their lives change dramatically as they take on adult roles. Young girls may get married and forced to move to their husband's home where they conduct domestic work and are exposed to high levels of air pollution from cooking. They are also more likely to become parents themselves. Many girls and boys drop out of school to work near their home or migrate within the country or abroad. They face risks throughout the journey and often work in precarious forms of labour. Among them, the unaccompanied adolescents face even greater risks than those who move with their parents. When parents migrate, despite increases in wealth from remittances, child and adolescent mental and physical health tends to worsen. With evidence mostly from the South Asian context, Dr Devakumar will explain detrimental impact of parental migration on left-adolescents and raise the importance of policy makers and health-care professionals on taking action to improve the health planning targeting of these young people.